Analysis Of The Coefficien Of Performance (COP) Freezer Produced By Solar Cell - Sudirman Lubis; Rafsanzani Pane (International Journal of Science, Technology & Management, 2021)
The use of freezer machines has now become a necessity for the wider community, because it is very helpful for humans in everyday life. The cooling load given greatly affects the performance of the freezer, both in terms of electrical energy consumption and the ability to increase system usage time. The greater the cooling load will increase the use of electrical energy during operation. This is very worrying in the future where the issue of depleting fossil energy sources which is currently a priority for producing electrical energy is increasing and filling the media. In recent years, solar energy has been rumored to be the answer to this problem. Where heat energy from the sun is used to move protons and electrons in a solar panel media to produce electrical energy that can be used for the needs of many people. This has become the attraction of researchers to make an innovation in the use of solar energy in a freezer system. Judging from the research roadmap related to solar energy and the vapor compression system in the freezer that was launched in the last few years, not many innovations have been carried out in the use of energy sources. The cooling load to be used will be adjusted to the capacity of the energy source used, which is 410 WP. With the capacity of the freezer that is used with a power of 1/4 PK which will increase its ability/ efficiency to be used and replace the paid electric energy freezer. This is expected to be useful for the public and contribute knowledge and help realize the university roadmap in the future.